Darrieussecq's mind - Kemp, S (Oxford University Press, 2008)
From Naissance des fantômes onwards, Marie Darrieussecq's representation of the self draws heavily on the materialist mind/brain model of cognitive science. Her fiction makes use of the disciple's discourse with and against the grain, creating micro-narratives of the mind's surface level and present moment which contrast sharply with more familiar psychoanalytic perspectives. Narrative form in Darrieussecq, I argue, can be characterized as a stream-of-consciousness, which, while failing to conform to the literary model set by Dujardin and Joyce, is in fact closer to the original psychological conception of the term. The article concludes by examining Darrieussecq's model of the mind in the context of France's current 'guerre des psys' between cognitive science and psychoanalysis.